Formative evaluation — an experience of learning and teaching innovation - Alba-Dorado, María Isabel (IATED Academy, 2018)
Nowadays we find ourselves with a scenario marked by a training model that is increasingly complex and extensive over time, which differs considerably from what has been done so far. This raises the need to rethink, review and reconsider the teaching and learning model of the current universities with the aim of "designing" a new teaching model that responds to the new emerging training needs demanded by society at the beginning of the 21st century. These changes in the training model strongly affect the current evaluation processes as it changes not only the way in which it develops, but also changes the object of evaluation, but above all changes the role that evaluation plays in the improvement of said learning processes. The evaluation acquires a new formative dimension, integrating itself in these processes with the objective of regulating them, reorienting them and improving them. To know in greater depth relative theoretical aspects about how this formative evaluation is developed, the agents that intervene or to know its implementation through an experience of university teaching innovation will be the objective of this paper.
Keywords: Formative evaluation; Learning; Architecture; Teaching innovation; Teaching